PRAGMATIC ILLOCUTIONARY ACTS USED IN ENGLISH SPEECHES YOUTUBE CHANNEL - Maharani, Fakhira Anisa; Rohbiah, Tatu Siti; Perdana, Purnama Rika (Metahumaniora, 2025)
This research discusses about the illocutionary act types which were performed on English Speeches YouTube Channel. The purpose of this study is to find out the types and to know how illocutionary acts used in English Speeches YouTube Channel. This research used qualitative descriptive and using Searle’s illocutionary act theory. The subject of this research was three videos that was uploaded by English Speeches on YouTube. This research finding 80 data that has been analyzed from three videos English Speeches YouTube Channel. The researcher found five type of illocutionary acts, the first is assertive illocutionary act, the second is commissive illocutionary act, the third is directive illocutionary act, the fourth is expressive illocutionary act, and the last one is declaration illocutionary act. Based on the analysis, the assertive act has the highest frequency of use among the others; there are 50 data out of 80 data found. Meanwhile, only 2 data found on commissive act and 2 data found on declarative act, has a lowest frequency of use among others.